Mountain Ultra-Marathon (UTMB) Impact on Usual and Emerging Cardiac Biomarkers - Le Goff, Caroline; Gergelé, Laurent; Seidel, Laurence; Cavalier, Etienne; Kaux, Jean-François (Frontiers in Cardiovascular Medicine, 2022)
The number of participants in ultra-marathons is increasing. However, the data regarding the impact of this type of exercise on the cardiovascular system are contradictory. In our study, 28 ultra-trail runners were enrolled. Blood samples were collected at three time points: immediately before, immediately after, and 7 days after the ultra-marathon. Different biomarkers were measured. Immediately after the race, the blood concentrations of the different cardiac and inflammatory biomarkers increased significantly. Interestingly, some biomarkers remained high even after 7 days of recovery.